Perancangan Meja Multifungsi pada Interior Small Living Space - Sidharta, Olivia; Honggowidjaja, Stephanus P; Kattu, Grace Setiati (Intra, 2018)
Due to the increasing price of land, the number of people who choose to live in the small houses, vertical housing such as apartments, flats and home office are also rising to provide their need for a place to live, thus it became one of the solution for the problem. With a limited living space and yet so many activities and needs, residents of small living space often experience problems of limited land and space condition. Therefore, a multifunctional furniture design that can accommodate several different activities will be needed, and one of them is a multifunctional table that can be used for makeup, read, write, use laptop and storage.